Feminist Pedagogy in Adult Learning Settings: A Literature Review of Articles in Adult Learning 1989-2022 - Lihua Shang; Lisa Baumgartner (Adult Education Research Conference, 2024)
Adopting an integrated literature review approach, this study analyzes how feminist pedagogy is manifested in articles in Adult Learning between 1989 and 2022.
Keywords: Feminist Pedagogy; adult education; Adult Learning